A Look into Motivations and Barriers to Student Involvement at the SHARING Clinic, a Student-Run Free Clinic - Benjamin McIntire; Susan Greni; Stephanie Radil; Melanie Menning (Journal of Student-Run Clinics, 2022)
Background: The University of Nebraska Medical Center (UNMC) is the host of a student-run free clinic (SRFC) called SHARING (Student Health Alliance Reaching Indigent Needy Groups) which has been serving uninsured patients in the Omaha metro area since 1997. Interprofessional student volunteers from medicine, pharmacy, nursing, medical laboratory science, physical therapy, and physician assis-tant programs operate under the supervision of an attending physician at each clinic. As a quality improvement project regarding volunteer recruitment, a survey of students was undertaken to de-termine the motivations and barriers to participation at SHARING.Methods: An anonymous, web-based survey hosted on Microsoft Forms was sent once to current UNMC students using their institutional email addresses. The survey included Likert scale as well as open- and closed-ended questions. Themes were identified in the responses to the open-ended ques-tions and tallied.Results: Out of 1,310 students surveyed, 137 participated for a response rate of 10.5%. Of those who responded, 65% had previously volunteered at SHARING, and their top motivators included gaining clinical experience and helping people in need of free healthcare. Likert scale questions indicated that volunteers were satisfied with their experiences and improved their empathy, clinical reasoning, and interprofessional skills. Of those who had not participated at SHARING, the top barriers were reported to be lack of time for volunteering and feeling inadequately prepared to offer medical care.Conclusion: Decreasing barriers to participation is important for a successful SRFC to be staffed by busy student volunteers. Suggestions for improved participation included a more detailed training program, more flexibility in clinic scheduling, academic incentives such as awards/recognition, and prioritization of advertising efforts. Due to the limited number of respondents to this survey, a wider study may give more detailed feedback that could lead to further quality improvement measures.